Owner evaluation of quality of life and mobility in osteoarthritic cats treated with amantadine or placebo. Issue 6 (June 2021) - Shipley, Hilary; Flynn, Kristi; Tucker, Laura; Wendt-Hornickle, Erin; Baldo, Caroline; Almeida, Daniel; Allweiler, Sandra; Guedes, Alonso
Objectives: The aim of the study was to determine if amantadine improves owner-identified mobility impairment and quality of life associated with osteoarthritis in cats. Methods: Using a blinded, placebo-controlled, randomized, crossover design, 13 healthy client-owned cats with clinical and radiographic evidence of osteoarthritis and owner-identified mobility impairment were studied. Cats received 5 mg/kg amantadine or placebo q24h PO for 3 weeks each with no washout period in between. Locomotor activity was continuously assessed with a collar-mounted activity monitor system, and owners chose and rated two mobility-impaired activities using a client-specific outcome measures (CSOM) questionnaire on a weekly basis. Locomotor activity on the third treatment week was analyzed with two-tailed paired t -tests. The CSOM scores were analyzed using a mixed-effect model and the Bonferroni post-hoc test. Owner-perceived changes in quality of life were compared between treatments using the χ 2 test. Statistical significance was set at P < 0.05. Results: Mean ± SD activity counts during the third week of each treatment were significantly lower with amantadine (240, 537 ± 53, 880) compared with placebo (326, 032 ± 91, 759). CSOM scores assigned by the owners were significantly better with amantadine on the second (3 ± 1) and third (3 ± 1) weeks compared with placebo (5 ± 2 and 5 ± 1, respectively). A significantly greater proportion of owners reported improvement in quality of life with amantadine compared with placebo. Conclusions and relevance: Amantadine significantly decreased activity, but improved owner-identified impaired mobility and owner-perceived quality of life in cats with osteoarthritis. Amantadine appears to be an option for the symptomatic treatment of osteoarthritis in cats.